Bodies on the Beach: Domesticates and Disasters in the Spanish Philippines 1750-1898. (1st August 2007) - Bankoff, Greg
Abstract : Disasters are simply a fact of life in the Philippines but their impact has largely been chronicled only in so far as it affects human society. Yet animals were also very much adversely affected by natural hazards especially domesticates often concentrated in large numbers as a result of their utility to human communities. This paper attempts to assess the extent of domestic livestock loss occasioned by natural hazard especially flood as well as the impact their deaths had on human communities. In particular, it applies the concept of vulnerability or whether the same factors that determine human exposure to risk on an individual or group basis such as age, gender, disability and occupation among others pertain to animals as well.